Effects of different quality of soil mixture on growth development of an important medicinal plant, Boesenbergia rotunda - Kamaludin A. Rashid,; Abu Bakar Mohd Daran,; Norzulaani Khalid,; Mahanom Jalil,; Yusmin Mohd Yusuf,; Shahril Efzueni Rozali,; Reza Farzin, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Growth and morphological development of Boesenbergia rotunda grown in different soil mixture were considered to determine the suitable growing media for the species. B. rotunda or fingerroot ginger is a highly important medicinal plant belonging to Zingiberaceae family. The rhizome and fingerroot structure of this species contains several bioactive compounds with various functional pharmaceutical activities. It can be vegetatively propagated through cutting rhizome and shows slow growth rate. This study provided some analysis and informative data on how the three types of typical soil (red soil (RS), black soil (BS) and sand (SS) can give important influences on the morphological and physiological development of the species. Fourteen different types of soil mixture with different mix ratio and quality were used as a growth medium. The effects of these treatments were implied based on the growth rate, evaluation in biomass quality of shoots, rhizomes and fingerroots, and photosynthetic pigment analysis. The highest quality growth of B. rotunda was established in the medium containing high percentage of RS and BS with low of SS. The growth rate of plant and photosynthetic pigment concentration were increased in the medium containing a high percentage of RS (50-100%) and BS (50-100%). The presence of a high percentage of BS in the medium was also significantly increased the biomass production of rhizome and fingerroots. The soil mixture might not make adverse effects on the shoots biomass except in medium containing more than 50% of SS. The physical characteristics (bulk density, porosity, water holding capacity and electrical conductivity) of the soil mixture were studied to determine the quality of an optimum combination of the growing medium. The synthetically evaluation index of the plant showed that the different type of soil mixture has a significant effect on growth development of B. rotunda that necessary in industrialization cultivation study.